Unified Selection System: What has the stricto sensu graduate researched? - Isabella Araújo Campos; Magnus Luiz Emmendoerfer (Arizona State University, 2020)
This article analyzed the policy of access to higher education of the Unified Selection System (SiSU - Sistema de Seleção Unificada, in Portuguese) conceived and implemented in Brazil. The choice of this theme refers to the political, economic and social importance of the population's access to this level of education. In methodological terms, a systematic review was carried out on this topic in the theses and dissertations catalog of CAPES, the main fostering agency for graduate studies in Brazil, due to incipience scientific publications on the topic. As results, in despite the decrease in the number of dissertations defended in the period 2015-2017, it cannot be said that discussions on the subject are running out, since there are few institutions involved. Through the thematic analysis, it can be inferred that the SiSU did not bring positive consequences for filling the vacancies. However, in the other analyzes, the results were divergent, so more research in the area will be necessary so that more accurate inferences can be made. The results of this research aim to contribute to the improvement of the debate on public policies for access to higher education in emerging and developing countries in the southern hemisphere.